PRELIMINARY INVESTIGATION OF THE LAND SUBSIDENCE PHENOMENA OCCURRING AT THE INDUSTRIAL-COMMERSIAL AREA OF ELEONAS, ATHENS, GREECE - Kaitantzian, A.; Loupasakis, C. (Bulletin of the Geological Society of Greece, 2016)
Land subsidence is a common phenomenon occurring in several regions worldwide. The current work focus on the industrial-commersial area of Eleonas, Athens, where vertical displacements were identified by Persistent Scatterer Interferometry (PSI) analysis. The rate of deformation in the study area according to the PSI results, during the period from May 1992 to December 2000, ranged between -1.5 and -10 mm/yr. The evaluation of the geological, geotechnical and hydrogeological conditions of the area combined with the PSI data provided substantial information for the interpretation of the land subsidence phenomenon. Also, the knowledge of the land use distribution and the activities taking place in the area helped the detection of its causal factors.